The high prevalence and impact of rheumatic heart disease in pregnancy in First Nations populations in a high-income setting: a prospective cohort study. - Sullivan, EA; Vaughan, G; Li, Z; Peek, MJ; Carapetis, JR; Walsh, W; Frawley, J; Rémond, M; Remenyi, B; Jackson Pulver, L; Kruske, S; Belton, S; et al. (Wiley, 2020)
OBJECTIVE:To describe the epidemiology of rheumatic heart disease (RHD) in pregnancy in Australia and New Zealand (A&NZ). DESIGN:Prospective population-based study. SETTING:Hospital-based maternity units throughout A&NZ. POPULATION:Pregnant women with RHD with a birth outcome of ≥20 weeks of gestation between January 2013 and December 2014. METHODS:We identified eligible women using the Australasian Maternity Outcomes Surveillance System (AMOSS). De-identified antenatal, perinatal and postnatal data were collected and analysed. MAIN OUTCOME MEASURES:Prevalence of RHD in pregnancy. Perinatal morbidity and mortality. RESULTS:There were 311 pregnancies associated with women with RHD (4.3/10 000 women giving birth, 95% CI 3.9-4.8). In Australia, 78% were Aboriginal or Torres Strait Islander (60.4/10 000, 95% CI 50.7-70.0), while in New Zealand 90% were Māori or Pasifika (27.2/10 000, 95% CI 22.0-32.3). One woman (0.3%) died and one in ten was admitted to coronary or intensive care units postpartum. There were 314 births with seven stillbirths (22.3/1000 births) and two neonatal deaths (6.5/1000 births). Sixty-six (21%) live-born babies were preterm and one in three was admitted to neonatal intensive care or special care units. CONCLUSION:Rheumatic heart disease in pregnancy persists in disadvantaged First Nations populations in A&NZ. It is associated with significant cardiac and perinatal morbidity. Preconception planning and counselling and RHD screening in at-risk pregnant women are essential for good maternal and baby outcomes. TWEETABLE ABSTRACT:Rheumatic heart disease in pregnancy persists in First Nations people in Australia and New Zealand and is associated with major cardiac and perinatal morbidity.